2011
DOI: 10.1007/s11010-011-1096-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-conditioning protecting rat cardiomyocytes from apoptosis via attenuating calcium-sensing receptor-induced endo(sarco)plasmic reticulum stress

Abstract: Our previous studies demonstrated that caclium-sensing receptor (CaR) stimulation elicited phospholipase C (PLC)-mediated inositol triphosphate (IP(3)) formation, leading to an elevation in [Ca(2+)](i) released from the endo(sarco)plasmic reticulum (ER) to induce ER stress and perturbations of ER function, which cause cardiomyocyte apoptosis during ischemia/reperfusion (I/R). The aim of this study was to determine whether the protection of post-conditioning (PC) from I/R heart injury involved relieving calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The digested cells were neutralized by the addition of DMEM medium containing 10% fetal bovine serum. NRCMs were separated by differential attachment and cultured at a density of 500 cells per mm 2 . At 24 h of culture, cellular attachment and individual cell beating were observed, while monolayer myocardial cells and synchronous pulsation of cell clusters were observed at 48 h of culture.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The digested cells were neutralized by the addition of DMEM medium containing 10% fetal bovine serum. NRCMs were separated by differential attachment and cultured at a density of 500 cells per mm 2 . At 24 h of culture, cellular attachment and individual cell beating were observed, while monolayer myocardial cells and synchronous pulsation of cell clusters were observed at 48 h of culture.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, endoplasmic reticulum (ER) stress has been shown to induce cardiomyocyte apoptosis during ischemia/reperfusion . During protein synthesis, 25% of cellular reactive oxygen species (ROS) such as H 2 O 2 are produced in the ER resulting from the activity of oxidoreductases, a family of proteins that catalyse protein folding .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, stimulation of Ca 2+ release from the SR was demonstrated to be beneficial by conserving myocyte contractility [31]. Contradictory findings were demonstrated by postconditioning studies showing that blockade of Ca 2+ release from the SR is protective [18]. This controversy concerning the role of Ca 2+ release from SR contributes to the ambiguity regarding the role of Ca 2+ in postconditioning.…”
mentioning
confidence: 99%
“…It’s even reported that during cardiac I/R process, CaSR was over-expressed, which was involved in the calcium overload induced cardiomyocyte apoptosis (Zhang et al, 2006). Although CaSR activation during ischemic preconditioning may be myocardial protective in mice (Sun & Murphy, 2010), it has been well documented that IPC achieved myocardium protection partially by CaSR inhibition (Dong et al, 2010; Gan et al, 2012). …”
Section: Introductionmentioning
confidence: 99%